Analysis of beampattern dwell time for planar frequency diverse array - Hui Chen; Zi‐Hao Li; Wen‐Qin Wang (IET Signal Processing)
Abstract Frequency diverse array (FDA) has received much attention due to its both range–angle‐dependent beampattern. However, most of the existing works focus on the linear FDA, and time‐varying characteristics of its beampattern only give a rough qualitative analysis. To further study the spatial beampattern dwell time issues, the pulsed‐planar FDA measurement model is first given, and then, the quantitative analysis of beam dwell time which can be affected by observation point location (azimuth, elevation, and range) and array antenna frequency offset coding method for a given pulse transmitting signal is presented. Finally, the theoretical analysis is proved to be consistent with the simulations.